2014
DOI: 10.1016/j.jped.2013.12.012
|View full text |Cite
|
Sign up to set email alerts
|

TLR-2 and TLR-4 expression in monocytes of newborns with late-onset sepsis

Abstract: This study investigated the innate immune response in septic newborns. Septic newborns that relied almost exclusively on the innate immune system showed little in vivo response at monocyte activation, suggesting impaired immune response and increased susceptibility to infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…During the initiation of the inflammatory septic process, changes occur in the expression levels of numerous inflammatory mediators, including an increase in the expression levels of pro-inflammatory cytokines IL-8, IL-6 and IL-1β, and anti-inflammatory cytokine IL-10 (26). Sepsis and endotoxemia have been associated with increased production of IL-1β, IL-6, IL-8, and TNF-α in the plasma and colon tissue (26). The results of the present study showed that the presence of LPS resulted in increased expression of IL-1β, IL-6, IL-8, TNF-α in the plasma and colon tissue.…”
Section: Discussionsupporting
confidence: 56%
“…During the initiation of the inflammatory septic process, changes occur in the expression levels of numerous inflammatory mediators, including an increase in the expression levels of pro-inflammatory cytokines IL-8, IL-6 and IL-1β, and anti-inflammatory cytokine IL-10 (26). Sepsis and endotoxemia have been associated with increased production of IL-1β, IL-6, IL-8, and TNF-α in the plasma and colon tissue (26). The results of the present study showed that the presence of LPS resulted in increased expression of IL-1β, IL-6, IL-8, TNF-α in the plasma and colon tissue.…”
Section: Discussionsupporting
confidence: 56%
“…Two important receptors involved in recognizing pathogenic ligands and maintaining host defense are TLR2 and TLR4, which predominantly bind to constituents of gram positive and gramnegative bacteria respectively (79). However, there are several studies showing that a dysregulation in these receptors can cause excess pro-inflammatory cytokines and chemokines, leading to autoimmunity, sepsis and multi-organ dysfunction (80,81).…”
Section: Toll Like Receptorsmentioning
confidence: 99%
“…Patients with acute coronary syndromes have an increased expression of TLR-2 and TLR-4 on circulating monocytes [26,27]. During sepsis in newborns, monocytes express higher levels of TLR-4 [28]. Monocytes from HIV-infected patients displayed enhanced expression of TLR-2 [29].…”
Section: Monocyte Surface Biomarkersmentioning
confidence: 99%